Transcriptomic analysis of a near‐isogenic line of melon with high fruit flesh firmness during ripening. (9th September 2020) - Zarid, Mohamed; García‐Carpintero, Victor; Esteras, Cristina; Esteva, Juan; Bueso, María C; Cañizares, Joaquín; Picó, María B; Monforte, Antonio J; Fernández‐Trujillo, J Pablo
Abstract: BACKGROUND: A near‐isogenic line (NIL) of melon (SC10‐2) with introgression in linkage group X was studied from harvest (at firm‐ripe stage of maturity) until day 18 of postharvest storage at 20.5 °C together with its parental control ('Piel de Sapo', PS). RESULTS: SC10‐2 showed higher flesh firmness and whole fruit hardness but lower juiciness than its parental. SC10‐2 showed a decrease in respiration rate accompanied by a decrease in ethylene production during ripening, both of which fell to a greater extent than in PS. The introgression affected 11 volatile organic compounds (VOCs), the levels of which during ripening were generally higher in SC10‐2 than in PS. Transcriptomic analysis from RNA‐Seq revealed differentially expressed genes (DEGs) associated with the effects studied. For example, 909 DEGs were exclusive to the introgression, and only 23 DEGs were exclusive to postharvest ripening time. Major functions of the DEGs associated with introgression or ripening time were identified by cluster analysis. About 37 genes directly and/or indirectly affected the delay in ripening of SC10‐2 compared with PS in general and, more particularly, the physiological and quality traits measured and, probably, the differential non‐climacteric response. Of the former genes, we studied in more detail at least five that mapped in the introgression in linkage group (LG) X, and 32 outside it. CONCLUSION: There is an apparent control of textural changes, VOCs and fruit ripening by an expression quantitative trait locus located in LG X together with a direct control on them due to genes presented in the introgression ( Cm TrpD, Cm NADH1, Cm TCP15, Cm GDSL esterase/lipase, and Cm HK4‐like) and Cm NAC18. © 2020 Society of Chemical Industry